2021
DOI: 10.1002/cti2.1364
|View full text |Cite
|
Sign up to set email alerts
|

SKI‐G‐801, an AXL kinase inhibitor, blocks metastasis through inducing anti‐tumor immune responses and potentiates anti‐PD‐1 therapy in mouse cancer models

Abstract: Objectives AXL‐mediated activation of aberrant tyrosine kinase drives various oncogenic processes and facilitates an immunosuppressive microenvironment. We evaluated the anti‐tumor and anti‐metastatic activities of SKI‐G‐801, a small‐molecule inhibitor of AXL, alone and in combination with anti‐PD‐1 therapy. Methods In vitro pAXL inhibition by SKI‐G‐801 was performed in both human and mouse cancer cell lines. Immunocompetent mouse models of tumor were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In vivo pharmacologic inhibiting pan-TAM Tyrosine Kinases, TYRO3, AXL, and MERTK, diminishes MDSC suppressive capability, promotes CD8 + T cell infiltration, slows tumor growth, and augments anti-PD-1 immunotherapy [ 247 249 ]. Consistently, another AXL kinase inhibitor, SKI-G-801, blocks metastasis through inducing anti-tumor immune responses and potentiates anti-PD-1 therapy in multiple mouse cancer models (including B16F10 melanoma, CT26 colon, 4T1 breast, TC1 and C3PQ lung cancer models) [ 250 , 251 ]. Similarly, combining AXL kinase inhibitor R428 with anti–PD-1 in a mouse HER2 + breast cancer model reduces the primary tumor and metastatic burdens [ 171 ].…”
Section: Potential Strategies Targeting Emp To Enhance the Icb Responsementioning
confidence: 99%
See 2 more Smart Citations
“…In vivo pharmacologic inhibiting pan-TAM Tyrosine Kinases, TYRO3, AXL, and MERTK, diminishes MDSC suppressive capability, promotes CD8 + T cell infiltration, slows tumor growth, and augments anti-PD-1 immunotherapy [ 247 249 ]. Consistently, another AXL kinase inhibitor, SKI-G-801, blocks metastasis through inducing anti-tumor immune responses and potentiates anti-PD-1 therapy in multiple mouse cancer models (including B16F10 melanoma, CT26 colon, 4T1 breast, TC1 and C3PQ lung cancer models) [ 250 , 251 ]. Similarly, combining AXL kinase inhibitor R428 with anti–PD-1 in a mouse HER2 + breast cancer model reduces the primary tumor and metastatic burdens [ 171 ].…”
Section: Potential Strategies Targeting Emp To Enhance the Icb Responsementioning
confidence: 99%
“… [ 294 ] Lung cancers Sensitized mesenchymal lung cancer cells to CTLs and NK cells via intracellular adhesion molecule-1 (ICAM-1)/leukocyte function-associated antigen-1 (ICAM1/LFA-1) and UL16 binding protein 1 (ULBP1)/ natural killer group 2, member D (NKG2D) interactions. [ 246 ] BMS-777607 Murine Model of Triple-Negative Breast Cancer Blocks macrophage efferocytosis and Gas6-PS–opsonized apoptotic cell, and enhances anti-PD-1 mAb efficacy via up-regulating PD-L1 expression [ 249 ] SKI-G-801 B16F10 melanoma, CT26 colon and 4T1 breast model Blocks metastasis through inducing CD8 + T cells, decreasing M2 macrophage and potentiates anti-PD-1 therapy [ 250 ] TC1 and C3PQ mouse tumor models Improves efficiency of anti-PD-1 therapy, exhibiting increased proportion of effector memory helper T cells, CD86+ macrophages. [ 251 ] Enapotamab vedotin (EnaV) Melanoma and lung cancer models Induced ICB benefit and promoted the induction of a memory-like phenotype in cytotoxic T cells.…”
Section: Potential Strategies Targeting Emp To Enhance the Icb Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In syngeneic murine glioblastoma models, targeting AXL plus PD-1 effectively prolonged the survival of glioblastoma-bearing mice ( 183 ). A recent study has reported similar results using a new selective AXL/FLT3 inhibitor, SKI-G-801 in B16F10 melanoma, CT26 colon, and 4T1 BCa models ( 185 ). The results highlight the potential of AXL targeting to overcome anti-PD-1 therapy resistance.…”
Section: Evidence For Axl-mediated Time Remodeling Immunosuppression ...mentioning
confidence: 60%
“… 17 Therefore, AXL inhibition and ICI may synergize to create improved anti-tumor immune responses, and this has been demonstrated with anti-PD-1 therapy in pre-clinical tumor models. 18 Clinically, in patients with melanoma, AXL transcript levels were significantly correlated with resistance to anti-PD-1 checkpoint therapy, 19 , 20 highlighting the importance of investigating AXL inhibitors in the clinic with the goal of increasing ICI efficacy.…”
Section: Introductionmentioning
confidence: 99%